“Iedzimtā grēka” koncepts kristīgajā baznīcā periodā pirms Augustīna - Galvāns, Roberts (Latvijas Universitāte, 2020)
Šajā darbā apkopotas un analizētas nozīmīgāko baznīctēvu, kuri darbojušies laika posmā starp kristīgās baznīcas izveidošanās un pirms Augustīna teologa karjeras sākuma, paustās nostādnes attiecībā uz konceptu "iedzimtais grēks". Pētījuma rezultātā, autors konstatēs, ka, lai gan pirmajos kristietības pastāvēšanas gadsimtos nav bijis strikti definēts, koncepts "iedzimtais grēks" ir jau pastāvējis. Darbā secināts, ka dažādu teoloģisko sadursmju un domas attīstības rezultātā baznīctēviem nācies konkretizēt kristīgās mācības robežas, izveidojot noteiktāku konceptu "iedzimtais grēks", taču bez vispārējo baznīcas koncilu akcepta.

The concept of "original sin" in the Christian church in the period before Augustine The Master thesis statement: "The concept of "original sin" was not invented and implemented by Augustine, but existed and used in the Christian church before him." This work summarizes and analyzes the positions of the most important church fathers who worked in the period between the formation of the Christian Church and before the beginning of the career of Augustine theologian regarding the concept of "original sin". As a result of the study, it will be found that, although it was not strictly defined in the first centuries of Christianity, the concept of "original sin" did exist. The paper concludes that as a result of various theological clashes and the development of thought, the Church Fathers have had to concretize the boundaries of Christian teaching, creating a more definite concept of "original sin", but without the general acceptance of church councils.
The concept of "original sin" in the Christian church in the period before Augustine
Keywords: Teoloģija un reliģiju zinātne; iedzimtais grēks; baznīctēvi; senbaznīca; patristika